Extended Reach 10 Gb/s Transmission with an Optical I/Q Modulator Using VCSELs over OFDM-Based Multimode Fiber Link - Deepak Kedia; Monika Nehra (International Journal of Optics)
This paper investigates the possibilities of extending the reach of a 10 Gb/s orthogonal frequency division multiplexing- (OFDM-) based multimode fiber (MMF) link with an optical I/Q modulation technique through vertical cavity surface emitting lasers (VCSELs). The proposed I/Q modulation technique comprises two VCSELs in a 90° hybrid combination to produce I/Q modulated OFDM signal. The results show the excellent performance (in terms of BER and Q factor) of the direct-detection optical- (DDO-) OFDM system with the proposed I/Q modulation in comparison to the direct modulation case. The proposed system is able to achieve worst-case BER of about 1.8616 × 10−3 and Q factor of about 10.9949 dB over a 5 km MMF link. The I/Q modulation technique in the DDO-OFDM system has further been investigated for extending the transmission reach of the MMF link using multispan configuration.